A critical analysis of media discourse on the South African broadband policy - Vergeer, Johannes Willem (Department of Information Systems, 2014)
Broadband Internet access promises a number of socio-economic benefits to citizens of developing countries like South Africa (SA). However poor policy outcomes of Information and Communication Technology (ICT), particularly in the area of poverty alleviation are evident in SA. This study utilizes Citation Analysis and Habermasien Critical Discourse Analysis (CDA) for understanding media discourse on the SA Broadband Policy formulation process and focuses on the impact and implications of the discourse. Highlighting distortions in these discourses will enable the general public and decision makers to formulate a better informed opinion and should facilitate better understanding and decision making on the costs, need and relevance of broadband access.